Tools for the evaluation of web accessibility: A systematic literature mapping - Agüero Flores, Patricia (2020)
In recent years, different tools have been proposed to automate the evaluation of the web contents accessibility criteria proposed by the World Wide Web Consortium (W3C). These tools can verify that a website complies with web accessibility standards such as WCAG, but the results of the evaluation may depend on the tool used. This study identifies and characterizes web accessibility assessment tools through a systematic literature mapping. A total of 50 articles were analyzed. We report the accessibility criteria evaluated by each tool as well as the main challenges related to the evaluations.